First European Olympic Games in Baku : New Articulation of Azerbaijani Identity? - Valiyev, Anar (Palgrave Macmillan, 2016)
Cities competed for the honor of hosting the various sport events throughout the twentieth century. Within that context, development connected with sports was regarded as part of a strategy which cities followed to create cultural and leisure capital to reinforce place promotion and consumption- based economic development’ (Bourdieu 1997; Euchner 1999; Gospodini 2006). Seoul, Barcelona, London and many other cities used large-scale sport events not only to advance economic development but also to put themselves into the list of grand cities. Although such development often tends to absorb a disproportionate share of resources that hypothetically might go to other projects or places in the city’ (Eisinger 2000), still a number of developing cities are promoting this cultural dimension and remarking cities as ‘places to play’ (Eisinger 2000). Cities try to compete to get noticed. As the literature suggests (Gotham 2005), urban spectacles or one-time events similar to Olympic Games are large-scale spectacular productions where advertisement, entertainment, TV and mass media feature increasingly to stimulate consumer demand and tourism-oriented development. Spectacular urban development agendas are frequently justify ed on the basis of developmentalist thinking, which equates national progress and ‘modernity’ with economic development, ‘defined for policy purposes in terms of growth, productivity, and competitiveness rather than in terms of welfare’ (Olds and Yeung 2004: 511). These types of events, a key example of which is the Olympic Games, are of short-term time span and demand massive investments. The classic example of the failure of the Montreal 1976 Olympics, which left the city with ‘white elephant facilities’ and financial burden (Chalkley and Essex 1999), have haunted policy makers for the last couple of decades. Nevertheless, such events attract a large number of tourists and high level of international media providing opportunity for host nations, especially small ones, to showcase their achievements. Moreover, this kind of event boosts national pride and even identity. The first European Olympic Games in Baku, held in June of 2015, became one such event. Authorities in Azerbaijan assured the population that hosting the European Games would reinvigorate self-assurance that the nation was capable of staging mega events. As Grant put it: ‘Horizons of pleasure, of excitement, of possibility are all wrapped up in such projects. It buys the government an extraordinary amount of time’ among locals for its policies’ (Eurasianet 2005). However, it might be highly speculative to claim that sport events can significantly impact identity building. Thus, we can argue that the government’s strategy was not to build identity but to promote the country and the city, and to build a positive image of Azerbaijan, which did not stipulate meaningful domestic changes. The purpose of this chapter is to examine how Baku, a city that never hosted a major global event, develops its potential for sports as part of its quality-of-life and place-making agenda. I examine urban transformations in Baku, especially in terms of its strategy of becoming a ‘place to play’. In this context I also discuss the correlation between identity building and marketing the place, and will try to answer the question of whether the government was able to succeed in either of these strategies. This is followed by discussion of issues of urban policies, national identity and the impact of European Olympic Games on urban transformations within the city.
Mega events in Post-Soviet Eurasia : shifting borderlines of inclusion and exclusion
Keywords: Hosting of sporting events -- Azerbaijan.; Hosting of sporting events -- Political aspects -- Azerbaijan.